2021
DOI: 10.1007/jhep09(2021)095
|View full text |Cite
|
Sign up to set email alerts
|

Gedanken experiments at high-order approximation: Kerr black hole cannot be overspun

Abstract: Sorce and Wald proposed a new version of gedanken experiments to examine the weak cosmic censorship conjecture (WCCC) in Kerr-Newmann black holes. However, their discussion only includes the second-order approximation of perturbation and there exists an optimal condition such that the validity of the WCCC is determined by the higher-order approximations. Therefore, in this paper, we extended their discussions into the high-order approximations to study the WCCC in a nearly extremal Kerr black hole. After assum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Recently, by taking into account the second-order perturbations that comes from the matter fields, Sorce and Wald showed that the Kerr-Newman black hole cannot be destroyed [34]. Subsequent systematic works further support the result that the event horizon cannot be destroyed by this kind of gedanken experiment [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, by taking into account the second-order perturbations that comes from the matter fields, Sorce and Wald showed that the Kerr-Newman black hole cannot be destroyed [34]. Subsequent systematic works further support the result that the event horizon cannot be destroyed by this kind of gedanken experiment [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, by taking into account the second-order perturbations that comes from the matter fields, Sorce and Wald showed that the Kerr-Newman black hole cannot be destroyed [32]. Subsequent systematic works further support the result that the event horizon cannot be destroyed by this kind of gedanken experiment [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%